AN ANALYSIS OF WRITTEN ERRORS; A CASE OF SECOND SEMESTER STUDENTS OF ENGLISH - Hayati, Wardah (LET: Linguistics, Literature and English Teaching Journal, 2019)
Errors are envitable happen during the process of learning a language. Students of English majoring in UIN A Antasari also frequently make errors in their witten respon during reading comprehension class. By analying written paper of these 28 students the researcher aims to know the areas as well as the types ot their errors. The analysis on 114 student written  errors shows that the students made errors in the areas of to be/auxiliary, subject-verb agreement, lexical, preposition, noun clause, possessive, verb, noun phrase construction, pluralization, and article. The most errors was in the area of tobe/ auxiliary with 34 errors while the least one is in article. Types of errors found in this study are misformation, omission, addition and misordering. The anlysis indicates that the errors are resulted from interlingual errors indicating interference from Bahasa.